Permanent draft genome sequence of the probiotic strain Propionibacterium freudenreichii CIRM-BIA 129 (ITG P20). Issue 1 (December 2016) - Falentin, Hélène; Deutsch, Stéphanie-Marie; Loux, Valentin; Hammani, Amal; Buratti, Julien; Parayre, Sandrine; Chuat, Victoria; Barbe, Valérie; Aury, Jean-Marc; Jan, Gwenaël; Le Loir, Yves
Abstract Propionibacterium freudenreichii belongs to the classActinobacteria (Gram positive with a high GC content). This "Generally Recognized As Safe" (GRAS) species is traditionally used as (i) a starter for Swiss-type cheeses where it is responsible for holes and aroma production, (ii) a vitamin B12 and propionic acid producer in white biotechnologies, and (iii) a probiotic for use in humans and animals because of its bifidogenic and anti-inflammatory properties. Until now, only strain CIRM-BIA1T had been sequenced, annotated and become publicly available. Strain CIRM-BIA129 (commercially available as ITG P20) has considerable anti-inflammatory potential. Its gene content was compared to that of CIRM-BIA1 T. This strain contains 2384 genes including 1 ribosomal operon, 45 tRNA and 30 pseudogenes.